The 'C-suite' executive leader in sport : contemporary global challenges for elite professionals - Lawrence, Ian (Emerald Publishing Limited, 2021)
The 'C- Suite' Executive Leader in Sport explores the challenges of this unique role within elite professional sport. Taking a multidisciplinary approach, the book blends academic theory with practitioner interviews from leading figures working a range of elite sporting disciplines and organisations, enhancing understanding of the C- Suite executive within the world of elite sports, where the exploration of the role remains ambiguous and conflicted. The 'C- Suite' Executive Leader in Sport studies a range of issues including global sport governance and best practice, high performance organisations, masterminding innovation and change, diversity and inclusion, current and future key challenges faced by sports organisations, C- Suite leader education and professional development, and the future of the C- Suite leader in elite sport. Examining the lived experience of C- Suite executives, contributors analyse how this relates to existing research, seeking to inform and challenge those individuals responsible for identification, recruitment and promotion of C- Suite sports industry personnel. The book's findings have far reaching implications for analysis of C- Suite effectiveness and efficiency across sporting sectors.